Burden of infectious disease studies in Europe and the United Kingdom: a review of methodological design choices. (9th January 2023) - Charalampous, Periklis; Haagsma, Juanita A.; Jakobsen, Lea S.; Gorasso, Vanessa; Noguer, Isabel; Padron-Monedero, Alicia; Sarmiento, Rodrigo; Santos, João Vasco; McDonald, Scott A.; Plass, Dietrich; Wyper, Grant M. A.; Assunção, Ricardo; et al.
Abstract: This systematic literature review aimed to provide an overview of the characteristics and methods used in studies applying the disability-adjusted life years (DALY) concept for infectious diseases within European Union (EU)/European Economic Area (EEA)/European Free Trade Association (EFTA) countries and the United Kingdom. Electronic databases and grey literature were searched for articles reporting the assessment of DALY and its components. We considered studies in which researchers performed DALY calculations using primary epidemiological data input sources. We screened 3053 studies of which 2948 were excluded and 105 studies met our inclusion criteria. Of these studies, 22 were multi-country and 83 were single-country studies, of which 46 were from the Netherlands. Food- and water-borne diseases were the most frequently studied infectious diseases. Between 2015 and 2022, the number of burden of infectious disease studies was 1.6 times higher compared to that published between 2000 and 2014. Almost all studies (97%) estimated DALYs based on the incidence- and pathogen-based approach and without social weighting functions; however, there was less methodological consensus with regards to the disability weights and life tables that were applied. The number of burden of infectious disease studies undertaken across Europe has increased over time. Development and use of guidelines will promote performing burden of infectious disease studies and facilitate comparability of the results.